Association between control reminder message usage and patient adherence to follow-up appointments - Carina Rega Utomo; Adelia Rochma; Kurnia Puji Prastiwi (Journal of Clinical Nursing Studies and Practice, 2025)
Patient adherence to control schedules is key to successful chronic disease management. Non-adherence primarily caused by forgetfulness remains a major challenge in clinical practice. This study aimed to examine the association between the use of control reminder messages and patient adherence to follow-up appointments at Manguharjo’s Pulmonary Hospital. This quantitative correlational study with a cross-sectional design involved 161 patients (N=161) using a convenience sampling technique. Data were collected from medical records regarding reminder reception and attendance status. The Chi-Square test results showed a highly significant association between reminder use and patient adherence (p < 0.001). The adherence rate in the group that received reminders was 64.6%, substantially higher than the non-reminder group (35.4%). It is concluded that reminder messages are an effective intervention to mitigate forgetfulness and should be formally integrated into the care system. The main limitation is the cross-sectional design. Prospective Randomized Controlled Trials (RCTs) are recommended to establish causality and optimize message format.